The teenager's perception of parenting - Padayachy, Narissa (Department of Psychology, 2023)
This study is exploratory in nature. It aims to investigate the needs and experiences of teenagers, specifically in relation to their perception of their parents. In addition to the objective of exploration, the information serves as a guide to action. Therefore, the study makes recommendations for intervention as well as for future research. The methodologies used were those of the self-administered questionnaire and the focus group. Results were subsequently analysed on both the descriptive and the interpretative levels, which facilitated the process of making recommendations. In essence the two main things which teenagers appear to desire are: improved patterns of communication negotiation towards discipline the findings of this study suggest the implementation of parent education workshops.